Effect of menstrual cycle phase on sprinting performance - Tsampoukos, A.; Peckham, E. A.; James, R.; Nevill, M. E. (European Journal of Applied Physiology, 2010)
This study examined the effects of menstrual cycle phase (MCP) upon sprinting and recovery as well as upon metabolic responses to such exercise. Eight females performed a repeated 30-s sprint on a non-motorised treadmill interspersed with a 2-min rest in three phases of the MCP, follicular (low 17ß-estradiol and progesterone), just prior to ovulation (midcycle trial, highest 17ß-estradiol concentration and low progesterone) and in the luteal phase (high 17ß-estradiol and high progesterone). MCP was verified later by radioimmunoassay of 17ß-estradiol and progesterone. Peak power output (PPO) and mean power output (MPO) were unaltered (P > 0.05) due to MCP [PPO for sprint 1: 463 (18) W vs. 443 (15) W vs. 449 (18) W; PPO for sprint 2: 395 (17) W vs. 359 (16) W vs. 397 (17) W; MPO for sprint 1: 302 (15) W vs. 298 (13) W vs. 298 (14) W; MPO for sprint 2: 252 (10) W vs. 248 (10) W vs. 259 (12) W for follicular, midcycle and luteal trial, mean (SEM), respectively]. Similarly, percentage recovery of PPO and MPO (the PPO or MPO during sprint 2 expressed as a percentage of the PPO or MPO during sprint 1) was also unchanged (P > 0.05). Blood lactate, blood pH and plasma ammonia after sprinting and estimated plasma volume were also unaltered by MCP (P > 0.05). These findings suggest that hormonal fluctuations due to MCP do not interfere with maximal intensity whole body sprinting and the metabolic responses to such exercise.